On-Premise Signs and the North American Suburban Enclosed Shopping Mall - Craig Berger (Interdisciplinary Journal of Signage and Wayfinding, 2018)
The first fully enclosed modern suburban shopping mall, Southdale Center, opened in 1956 and immediately established a standard for how retailers and signs were to operate within their confines. Enclosed Malls were one of the first unique building types designed for suburban automotive environments and have been a key retail economic driver in the United States for seventy years. The mall also reflected economic changes in the country and the increasing separation of income classes. Malls established a variety of sign innovations over the years, from developing strict sign guidelines, to creating formal zones with shared modular systems. This report will explore the sign advances that marked each of the five stages of mall evolution impacted design and development. The report will also show how precedents established early in the history of mall development as a center for a broad range of incomes changed as malls began to segment by class.